Gene expression in hip soft tissues in incipient canine hip dysplasia and osteoarthritis. Issue 2 (27th December 2018) - Todhunter, Rory J.; Garrison, Susan J.; Jordan, Julie; Hunter, Linda; Castelhano, Marta G.; Ash, Kristian; Meyers‐Wallen, Vicki; Krotscheck, Ursula; Hayward, Jessica J.; Grenier, Jennifer
ABSTRACT: Canine hip dysplasia and developmental dysplasia of the human hip share demographic, phenotypic, and clinical features including the predisposition to develop osteoarthritis in affected joints. To support the results of genetic mapping studies for CHD and its concomitant osteoarthritis with functional information, we performed RNA‐seq on hip capsule and teres ligament of affected and unaffected dogs. RNA seq showed that expressed genes segregated according age, capsule or ligament, and hip phenotype. Expression of HHIP, DACT2, and WIF1 was significantly higher in capsule from control hips than dysplastic hips indicating a disruption of the hedgehog signaling pathway. Expression of SPON 1, a key component of the WNT pathway, was increased significantly in both dysplastic capsule and ligament while FBN2 and EMILIN3 were significantly increased in dysplastic capsule. Of genes associated with human hip osteoarthritis, expression of ACAN, IGF1, CILP2, COL11A1, COL8A1, and HAPLN was increased significantly in dysplastic capsule. The significant increase in expression of PLA2F, TNFRSF, TMEM, and IGFBP in dysplastic capsule indicated an injury response. Gene set enrichment analysis revealed that genes involved in extracellular matrix structure, epithelial to mesenchymal transition, myogenesis, growth factor signaling, cancer and immune pathways were enriched in dysplastic capsule. For teres ligament from dysplastic joints, genes in retinoic signaling pathways and those encoding extracellular matrix molecules, but not proteoglycans, were enriched. Hip tissues respond to abnormal mechanics early in dysplastic hip development and these pathways present targets for intervention in the early synovitis and capsulitis secondary to canine and human hip dysplasia. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:313–324, 2019.